Principal Management in Improving Teacher Work Culture at MI Darul Hikmah, Bone District - M. Syawal; Misykat Malik Ibrahim; Bustan Ramli; Muljono Damopolii; Andi Halimah (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
Teacher work culture is a key component in achieving educational quality at schools. School principals play a strategic role in shaping and improving productive work culture. This research aims to analyze the principal's management in enhancing teacher work culture at MI Darul Hikmah in Bone Regency. The research method employed a qualitative approach with a case study design, using data collection techniques through observation, interviews, and documentation. The research findings reveal that the principal applied a transformational approach through periodic supervision, motivation provision, and creating a collaborative work environment. Supporting factors include the principal's strong commitment, availability of learning facilities, and positive interactions among teachers. Meanwhile, inhibiting factors include teacher tardiness, high workloads with low compensation, and limited learning resources, particularly for the Merdeka Curriculum. To address these challenges, the principal implemented a duty roster system, personal approaches, and encouraged collaboration between senior and junior teachers. Additionally, the principal initiated teacher professionalism development programs through training and seminars to improve teaching quality. Regular evaluations were conducted to ensure the effectiveness of the implemented strategies. The research recommends strengthening coordination, improving evaluation systems, and developing sustainable programs to support productive teacher work culture.